The Crisis-Resilience of Services Trade - Borchert, Ingo; Mattoo, Aaditya (2012)
Much attention has focused on the impact of the current crisis on goods trade; hardly any on its impact on services trade. Using new trade data from the United States, and more aggregate data from other OECD countries, the authors show that services trade is weathering the current crisis much better than goods trade. As of February 2009, the value of US goods imports had declined year-on-year by 33 percent and the value of goods exports by 21 percent; services imports and exports each had declined by less than 7 percent. Within services, interesting patterns are emerging. Trade in goods-related transport services and crisis-related financial services has shrunk, as has expenditure on tourism abroad. But trade in a range of business, professional, and technical services is still increasing, with US exports growing even faster (at 10 percent) than US imports (at 7 percent). Developing countries like India, which are relatively specialized in business process outsourcing and information technology services, have suffered much smaller declines in total exports to the United States than countries like Brazil and China and regions like Africa, which are specialized in exports of goods, transport services, or tourism services. On the basis of new evidence from Indian services exporters, the authors suggest that services trade is buoyant relative to goods trade for two reasons: demand for a range of traded services is less cyclical, and services trade and production are less dependent on external finance. Even though few explicitly protectionist measures have so far been taken in services, the changing political climate and the widening boundaries of the state in crisis countries may introduce a national bias in firms' procurement and location choices.